Smørmarkederne i Cork og Kjøbenhayn.Foredrag i det kgl. Landh.-Selskab d. 17. Februar 1887. - Riitzou, Poul (Tidsskrift for Landøkonomi, 2018)
Smørmarkederne i Cork og Kjøbenhayn.Foredrag i det kgl. Landh.-Selskab d. 17. Februar 1887.